The clinical and economic burden of chronic obstructive pulmonary disease in the USA - Guarascio AJ; Ray SM; Finch CK; Self TH (Dove Medical Press, 2013)
Anthony J Guarascio,1 Shauntá M Ray,1 Christopher K Finch,2,3 Timothy H Self21University of Tennessee College of Pharmacy, Knoxville, 2University of Tennessee College of Pharmacy, Memphis, TN, USA; 3Methodist University Hospital, Memphis, TN, USAAbstract: Chronic obstructive pulmonary disease (COPD) is the third most common cause of death in the USA. In 2010, the cost of COPD in the USA was projected to be approximately US$50 billion, which includes $20 billion in indirect costs and $30 billion in direct health care expenditures. These costs can be expected to continue to rise with this progressive disease. Costs increase with increasing severity of disease, and hospital stays account for the majority of these costs. Patients are diagnosed with COPD following a multifactorial assessment that includes spirometry, clinical presentation, symptomatology, and risk factors. Smoking cessation interventions are the most influential factor in COPD management. The primary goal of chronic COPD management is stabilization of chronic disease and prevention of acute exacerbations. Bronchodilators are the mainstay of COPD therapy. Patients with few symptoms and low exacerbation risk should be treated with a short-acting bronchodilator as needed for breathlessness. Progression of symptoms, as well as possible decline in forced expiratory volume in the first second of expiration (FEV1), warrant the use of long-acting bronchodilators. For patients with frequent exacerbations with or without consistent symptoms, inhaled corticosteroids should be considered in addition to a long-acting beta2-agonist (LABA) or long-acting muscarinic antagonist (LAMA) and may even consist of "triple therapy" with all three agents with more severe disease. Phosphodiesterase-4 inhibitors may be an option in patients with frequent exacerbations and symptoms of chronic bronchitis. In addition to a variety of novel ultra-LABAs, LAMAs and combination bronchodilator and inhaled corticosteroid (ICS) therapies, other bronchodilators with a variety of mechanisms are also being considered, to expand therapeutic options for the treatment of COPD. With more than 50 new medications in the pipeline for the treatment of COPD, optimal management will continue to evolve and grow more complex as benefits of therapy are balanced with the limitations and needs of each patient.Keywords: chronic obstructive pulmonary disease, COPD, clinical burden, economic burden